Field military flexible wear-resistant reel power cable

CN115810442BActive Publication Date: 2026-10-27ANHUI YUANZHENG CABLE TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211510192.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-29
Publication Date
2026-10-27
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种野外军用柔软耐磨卷盘电源电缆,用于解决现有技术中的电缆外部设置的保护层耐磨性能与抗扭曲性能往往较差,在拖拽和弯曲时,电缆外部的保护层容易裂开损坏,电缆外部保护层的耐磨性能与抗扭曲性能有待进一步的提高的技术问题

Benefits of technology

[0028]1、本发明中的电缆,通过导电组件、加强筋、阻燃层、外衬相互配合,加强筋与导电组件均成螺旋状交联在一起,加强筋能够有效的填补导电组件之间的间隙的同时,在电缆受到外力被拉伸时,能够与导电组件一起分摊拉力,提高电缆的拉伸强度,热塑性硫化橡胶材料制成的加强筋其耐热性能与耐压缩变形性较好,在拉伸过程中能够防止导电组件在加强筋断裂前断裂,提高导电组件的拉伸强度,加强筋与导电组件呈螺旋状结构,能够提高电缆的韧性,方便对电缆进行弯曲。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115810442B_ABST
    Figure CN115810442B_ABST
Patent Text Reader

Abstract

The application discloses a field military soft wear-resistant reel power cable and belongs to the technical field of cable processing. The application is used to solve the technical problem that the wear resistance and the anti-twisting performance of the cable in the prior art need to be further improved. The field military soft wear-resistant reel power cable comprises a conductive assembly, the conductive assembly is composed of a plurality of tinned conductors, the plurality of tinned conductors are in spiral structures, and the plurality of tinned conductors are all provided with an insulating sleeve outside. A plurality of reinforcing ribs are alternately distributed between the plurality of tinned conductors. The application effectively improves the wear resistance and the bending performance of the cable, effectively improves the tensile strength and the flame-retardant grade of the cable, and is more suitable for field use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cable processing technology, specifically to a flexible, wear-resistant reel power cable for field military use. Background Technology

[0002] A cable is a conductor made of one or more mutually insulated conductors and an outer insulating protective layer, used to transmit electricity or information from one place to another. Cables are essential basic equipment for transmitting electrical energy, transmitting information, and manufacturing various motors, instruments, and meters, realizing electromagnetic energy conversion. They are a necessary basic product in the future electrified and information-based society. For convenient outdoor use, cables are often wound together to form a reel structure.

[0003] In existing technologies, outdoor military cables are often subjected to continuous and frequent reciprocating dragging during use, as well as damage from external environmental and mechanical forces. This causes the cables to be in a constant state of dynamic bending. Ordinary flexible cables lack internal support, and the conductors in the cables often experience yield fatigue, resulting in core breakage and a short service life. Furthermore, the wear resistance and torsion resistance of the outer protective layer of traditional cables are often poor. When dragged and bent, the outer protective layer of the cable is prone to cracking and damage. The wear resistance and torsion resistance of the cable's outer protective layer need to be further improved.

[0004] To address this technical deficiency, a solution is proposed. Summary of the Invention

[0005] The purpose of this invention is to provide a flexible and wear-resistant reel power cable for field military use, which solves the technical problem that the wear resistance and torsion resistance of the outer protective layer of the cable in the prior art are often poor, and the outer protective layer of the cable is prone to cracking and damage when dragged and bent, and the wear resistance and torsion resistance of the outer protective layer of the cable need to be further improved.

[0006] The objective of this invention can be achieved through the following technical solutions:

[0007] A flexible, abrasion-resistant reel power cable for field military use, comprising:

[0008] A conductive component, wherein the conductive component is composed of several tin-plated conductors, all of which are spiral-shaped and are covered with an insulating sleeve.

[0009] The reinforcing ribs are of several kinds, and the several reinforcing ribs are alternately distributed between multiple tin-plated conductors;

[0010] A flame-retardant layer is wrapped around the conductive components and reinforcing ribs;

[0011] The outer liner, which wraps around the flame-retardant layer, is made of polyurethane composite material.

[0012] Furthermore, the polyurethane composite material is made by melt extrusion of modified polyurethane, viscose fiber, polyvinyl chloride and additives mixed in a weight ratio of 20-30:4-6:20-30:1-2. The additives are made by uniformly mixing crosslinking agent and lubricant in a weight ratio of 1:1-1.5. The crosslinking agent is composed of one or more of trimethylolpropane, polyethylene glycol and p-toluenesulfonic acid, and the lubricant is composed of one or more of zinc stearate and calcium stearate.

[0013] Furthermore, the synthesis of the modified polyurethane includes the following steps:

[0014] S1. Weigh 100-200 parts by weight of octamethylcyclotetrasiloxane and 100-200 parts by weight of 1,3-bis(aminopropyl)tetramethyldisiloxane, add them to a three-necked flask and stir. Under nitrogen protection, raise the temperature of the three-necked flask to 100-110℃, add 0.2-0.4 parts by weight of catalyst to the three-necked flask, react for 10-14 hours, and then obtain intermediate I after post-treatment.

[0015] The synthesis reaction principle of intermediate I is as follows:

[0016]

[0017]

[0018] S2. Weigh 10-20 parts of melamine, 30-60 parts of deionized water, 8-16 parts of polyphosphoric acid and 15-30 parts of zinc phosphate solution by weight, add them to a three-necked flask and stir. Raise the temperature of the three-necked flask to 95-105℃ and react for 2-3 hours. After post-processing, intermediate II is obtained.

[0019] The synthesis reaction principle of intermediate II is as follows:

[0020]

[0021] S3. Weigh out 30-60 parts by weight of intermediate I, 30-60 parts by weight of intermediate II, 20-40 parts by weight of toluene-2,4-diisocyanate, 90-180 parts by weight of tetrahydrofuran, and 3-5 parts by weight of acetic acid. Add them to a three-necked flask and stir. React for 4-6 hours. After post-treatment, the modified polyurethane is obtained.

[0022] Furthermore, the catalyst in step S1 is one of tetramethylammonium hydroxide silanolate or tetraethylammonium hydroxide silanolate.

[0023] Furthermore, the post-processing operation of step S1 is as follows: after the reaction is completed, the temperature of the three-necked flask is raised to 138-142°C, and the mixture is distilled under reduced pressure until no liquid flows out. The distillate is discarded, and the temperature of the three-necked flask is raised to 150-155°C, and the mixture is distilled under reduced pressure to obtain intermediate I.

[0024] Furthermore, in step S2, the zinc phosphate solution is a phosphoric acid solution with a zinc content of 13 wt%, prepared by completely dissolving 2-4 parts by weight of zinc oxide in 13-26 parts by weight of phosphoric acid.

[0025] Furthermore, the post-processing operation of step S2 is as follows: after the reaction is completed, the system is cooled to room temperature, ammonia water is slowly added to the three-necked flask to adjust the pH of the reaction system in the three-necked flask to 6-7, the mixture is filtered, the filter cake is washed with an ammonia solution of pH 6-7 and then dried, the filter cake is placed in a drying oven at 90-110℃ and dried for 8-10 hours, then pulverized to obtain intermediate II.

[0026] Furthermore, the post-processing operation of step S3 is as follows: after the reaction is completed, add 90-180 parts by weight of drinking water to a three-necked flask, stir for 10-20 minutes, raise the temperature of the three-necked flask to 40-50°C, distill under reduced pressure until no liquid flows out, filter, rinse the filter cake with drinking water and dry it, place the filter cake in a drying oven at 100-120°C and dry it for 10-12 hours to obtain modified polyurethane.

[0027] The present invention has the following beneficial effects:

[0028] 1. The cable of this invention comprises conductive components, reinforcing ribs, a flame-retardant layer, and an outer liner that work together. The reinforcing ribs and conductive components are spirally cross-linked together. The reinforcing ribs can effectively fill the gaps between the conductive components and, when the cable is stretched by external force, can share the tensile force with the conductive components, thereby improving the tensile strength of the cable. The reinforcing ribs made of thermoplastic vulcanized rubber have good heat resistance and compression deformation resistance. During the stretching process, they can prevent the conductive components from breaking before the reinforcing ribs break, thereby improving the tensile strength of the conductive components. The spiral structure of the reinforcing ribs and conductive components can improve the toughness of the cable and facilitate bending of the cable.

[0029] 2. The cable sheath of this invention is composed of modified polyurethane, viscose fiber, polyvinyl chloride, and additives. Intermediate I, grafted onto the modified polyurethane, has a long, straight-chain structure containing numerous Si-O bonds. The silicon-oxygen chains are helical, exhibiting greater flexibility than C-C or Si-C bonds, resulting in excellent physical and mechanical properties. Furthermore, the bond energy of the silicon-oxygen bonds is greater than that of C-C or Si-C bonds, thus improving the cable's flexibility. Intermediate II, grafted onto the modified polyurethane, contains melamine and polyphosphate. Melamine and polyphosphate produce a synergistic effect. Melamine phosphate decomposes upon heating to generate a network polymer, making... The char formation rate of the polymer is greatly improved, which affects its melting behavior and thus improves the flame retardant rating of the cable. Intermediate I and Intermediate II are organically combined by reacting with the isocyanate groups on toluene-2,4-diisocyanate. Intermediate I has a long straight-chain structure that can cross-link with adjacent molecules, further improving the tensile strength of the cable. After the raw materials of the cable are mixed evenly, they are extruded by a screw extruder, and the modified polyurethane is evenly distributed on the outer lining of the cable to form a mesh support with silicon elements as nodes, thereby improving the cable's abrasion resistance, flexural performance, fire resistance and tensile strength. Attached Figure Description

[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0031] Figure 1 This is a partial structural diagram of the cable in this invention;

[0032] Figure 2 This is a schematic diagram of the front cross-sectional structure of the cable in this invention;

[0033] In the diagram: 1. Conductive component; 101. Tin-plated conductor; 102. Insulating sleeve; 2. Reinforcing rib; 3. Flame retardant layer; 4. Outer lining. Detailed Implementation

[0034] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] Example 1

[0036] This embodiment of a flexible, abrasion-resistant reel power cable for field military use includes:

[0037] The conductive component 1 is composed of several tin-plated conductors 101. The multiple tin-plated conductors 101 are all spiral structures, and the outside of the multiple tin-plated conductors 101 is covered with an insulating sleeve 102.

[0038] Reinforcing rib 2, there are several reinforcing ribs 2, and several reinforcing ribs 2 are alternately distributed among multiple tin-plated conductors 101;

[0039] Flame-retardant layer 3 is wrapped around the outside of conductive component 1 and reinforcing rib 2;

[0040] Outer liner 4 is wrapped around the outside of flame retardant layer 3 and is made of polyurethane composite material.

[0041] The reinforcing ribs are made of thermoplastic vulcanized rubber material, the flame retardant layer is made of flame retardant non-woven fabric, and the polyurethane composite material is made by melting and extruding a mixture of modified polyurethane, viscose fiber, polyvinyl chloride and additives in a weight ratio of 20:4:20:1. The additives are made by uniformly mixing trimethylolpropane and calcium stearate in a weight ratio of 1:1.

[0042] The synthesis of modified polyurethane includes the following steps:

[0043] S1. Weigh 100g of octamethylcyclotetrasiloxane and 100g of 1,3-bis(aminopropyl)tetramethyldisiloxane according to the weight parts, add them to a three-necked flask and stir. Under nitrogen protection, raise the temperature of the three-necked flask to 100℃, add 0.2g of tetramethylammonium hydroxide silanolate to the three-necked flask, react for 10h, and when the reaction is complete, raise the temperature of the three-necked flask to 138℃ and distill under reduced pressure until no liquid flows out. Discard the distillate, raise the temperature of the three-necked flask to 150-155℃ and distill under reduced pressure to obtain intermediate I.

[0044] S2. Preparation of zinc phosphate solution: Weigh 2g of zinc oxide and 13g of phosphoric acid and add them to a beaker. Stir until the zinc oxide is completely dissolved to obtain a zinc phosphate solution. Weigh 10g of melamine, 30g of deionized water, 8g of polyphosphoric acid and 15g of zinc phosphate solution by weight and add them to a three-necked flask. Stir and raise the temperature of the three-necked flask to 95℃. React for 2 hours until the reaction is complete. Cool the system to room temperature and slowly add ammonia water to the three-necked flask to adjust the pH of the reaction system in the three-necked flask to 6. Filter the mixture. Wash the filter cake with an ammonia solution of pH=6 and then dry it. Place the filter cake in a drying oven at 90℃ and dry it for 8 hours. Crush the mixture to obtain intermediate II.

[0045] S3. Weigh out 30g of intermediate I, 30g of intermediate II, 20g of toluene-2,4-diisocyanate, 90g of tetrahydrofuran, and 3g of acetic acid according to the weight ratio, add them to a three-necked flask and stir. After the reaction is complete, add 90g of drinking water to the three-necked flask and stir for 10min. A large amount of solid precipitates out. Raise the temperature of the three-necked flask to 40℃ and distill under reduced pressure until no liquid flows out. Filter the mixture, rinse the filter cake with drinking water and dry it under vacuum. Place the filter cake in a drying oven at 100℃ and dry it for 10h to obtain modified polyurethane.

[0046] Example 2

[0047] This embodiment of a flexible, abrasion-resistant reel power cable for field military use includes:

[0048] The conductive component 1 is composed of several tin-plated conductors 101. The multiple tin-plated conductors 101 are all spiral structures, and the outside of the multiple tin-plated conductors 101 is covered with an insulating sleeve 102.

[0049] Reinforcing rib 2, there are several reinforcing ribs 2, and several reinforcing ribs 2 are alternately distributed among multiple tin-plated conductors 101;

[0050] Flame-retardant layer 3 is wrapped around the outside of conductive component 1 and reinforcing rib 2;

[0051] Outer liner 4 is wrapped around the outside of flame retardant layer 3 and is made of polyurethane composite material.

[0052] The reinforcing ribs are made of thermoplastic vulcanized rubber material, the flame retardant layer is made of flame retardant non-woven fabric, and the polyurethane composite material is made by melting and extruding modified polyurethane, viscose fiber, polyvinyl chloride and additives mixed in a weight ratio of 25:5:25:1.5. The additives are made by uniformly mixing polyethylene glycol and zinc stearate in a weight ratio of 1:1.5.

[0053] The synthesis of modified polyurethane includes the following steps:

[0054] S1. Weigh 150g of octamethylcyclotetrasiloxane and 150g of 1,3-bis(aminopropyl)tetramethyldisiloxane according to the weight parts, add them to a three-necked flask and stir. Under nitrogen protection, raise the temperature of the three-necked flask to 105℃, add 0.3g of tetraethylammonium hydroxide silanolate to the three-necked flask, react for 12h, the reaction is complete, raise the temperature of the three-necked flask to 140℃, distill under reduced pressure until no liquid flows out, discard the distillate, raise the temperature of the three-necked flask to 152℃, distill under reduced pressure to obtain intermediate I;

[0055] S2. Preparation of zinc phosphate solution: Weigh 3g of zinc oxide and 20g of phosphoric acid and add them to a beaker. Stir until the zinc oxide is completely dissolved to obtain a zinc phosphate solution. Weigh 15g of melamine, 45g of deionized water, 12g of polyphosphoric acid and 23g of zinc phosphate solution by weight and add them to a three-necked flask. Stir and raise the temperature of the three-necked flask to 100℃. React for 2.5h until the reaction is complete. Cool the system to room temperature and slowly add ammonia water to the three-necked flask to adjust the pH of the reaction system in the three-necked flask to 7. Filter the mixture. Wash the filter cake with an ammonia solution of pH=7 and then dry it. Place the filter cake in a drying oven at 100℃ and dry it for 9h. Crush the filter cake to obtain intermediate II.

[0056] S3. Weigh out 45g of intermediate I, 45g of intermediate II, 30g of toluene-2,4-diisocyanate, 135g of tetrahydrofuran, and 4g of acetic acid according to the weight ratio, add them to a three-necked flask and stir. After the reaction is complete, add 135g of drinking water to the three-necked flask and stir for 15min. Raise the temperature of the three-necked flask to 45℃ and distill under reduced pressure until no liquid flows out. Filter the mixture, rinse the filter cake with drinking water and dry it under vacuum. Place the filter cake in a drying oven at 110℃ and dry it for 11h to obtain modified polyurethane.

[0057] Example 3

[0058] This embodiment of a flexible, abrasion-resistant reel power cable for field military use includes:

[0059] The conductive component 1 is composed of several tin-plated conductors 101. The multiple tin-plated conductors 101 are all spiral structures, and the outside of the multiple tin-plated conductors 101 is covered with an insulating sleeve 102.

[0060] Reinforcing rib 2, there are several reinforcing ribs 2, and several reinforcing ribs 2 are alternately distributed among multiple tin-plated conductors 101;

[0061] Flame-retardant layer 3 is wrapped around the outside of conductive component 1 and reinforcing rib 2;

[0062] Outer liner 4 is wrapped around the outside of flame retardant layer 3 and is made of polyurethane composite material.

[0063] The reinforcing ribs are made of thermoplastic vulcanized rubber material, the flame retardant layer is made of flame retardant non-woven fabric, and the polyurethane composite material is made by melting and extruding modified polyurethane, viscose fiber, polyvinyl chloride and additives in a weight ratio of 30:6:30:2. The additives are made by uniformly mixing p-toluenesulfonic acid and zinc stearate in a weight ratio of 1:1.2.

[0064] The synthesis of modified polyurethane includes the following steps:

[0065] S1. Weigh 200g of octamethylcyclotetrasiloxane and 200g of 1,3-bis(aminopropyl)tetramethyldisiloxane according to the weight parts, add them to a three-necked flask and stir. Under nitrogen protection, raise the temperature of the three-necked flask to 110°C, add 0.4g of tetramethylammonium hydroxide silanolate to the three-necked flask, react for 14h, the reaction is complete, raise the temperature of the three-necked flask to 142°C, distill under reduced pressure until no liquid flows out, discard the distillate, raise the temperature of the three-necked flask to 155°C, distill under reduced pressure to obtain intermediate I;

[0066] S2. Preparation of zinc phosphate solution: Weigh 4g of zinc oxide and 26g of phosphoric acid and add them to a beaker. Stir until the zinc oxide is completely dissolved to obtain a zinc phosphate solution. Weigh 20g of melamine, 60g of deionized water, 16g of polyphosphoric acid and 30g of zinc phosphate solution by weight and add them to a three-necked flask. Stir and raise the temperature of the three-necked flask to 105℃. React for 3 hours until the reaction is complete. Cool the system to room temperature and slowly add ammonia water to the three-necked flask to adjust the pH of the reaction system in the three-necked flask to 7. Filter the mixture and rinse the filter cake with an ammonia solution of pH=7. Dry the filter cake in a drying oven at 110℃ for 10 hours. Crush the filter cake to obtain intermediate II.

[0067] S3. Weigh 60g of intermediate I, 60 parts of intermediate II, 40g of toluene-2,4-diisocyanate, 180g of tetrahydrofuran, and 5g of acetic acid according to the weight ratio. Add them to a three-necked flask and stir. React for 6 hours. After the reaction is complete, add 180g of drinking water to the three-necked flask and stir for 20 minutes. Raise the temperature of the three-necked flask to 50℃ and distill under reduced pressure until no liquid flows out. Filter the mixture, rinse the filter cake with drinking water and dry it under vacuum. Place the filter cake in a drying oven at 120℃ and dry it for 12 hours to obtain modified polyurethane.

[0068] Comparative Example 1

[0069] The difference between this comparative example and Example 3 is that no reinforcing ribs were added to the cable, and no modified polyurethane was added to the outer lining material.

[0070] Comparative Example 2

[0071] The difference between this comparative example and Example 3 is that intermediate I was not added in the S3 operation step.

[0072] Comparative Example 3

[0073] The difference between this comparative example and Example 3 is that intermediate II was not added in the S3 operation step.

[0074] Performance testing:

[0075] The abrasion resistance, flexural strength, fire resistance, and tensile strength of the cables prepared by Examples 1-3 and Comparative Examples 1-3 were tested according to the standard GB / T5013.2-2008 "Rubber-insulated cables with rated voltage of 450 / 750V and below - Part 2: Test methods". The flame retardancy rating was tested according to the standard XF306.1-2007 "Flame-retardant and fire-resistant cables - Classification and requirements of plastic-insulated flame-retardant and fire-resistant cables - Part 1: Flame-retardant cables". The specific test results are shown in the table below:

[0076]

[0077] Based on the analysis of the data from Comparative Example 1 and Examples 1-3 in the table above, the cable material prepared by this invention exhibits significant improvements in tensile strength, flame retardancy, abrasion resistance, and flexural performance. The tensile strength in the examples is much higher than that in Comparative Example 1. This is because the reinforcing ribs added to the cable work in conjunction with the conductive components. When the cable is subjected to tensile force, the reinforcing ribs can distribute the tensile force, resulting in higher tensile strength in the cable of this invention. Furthermore, since melamine introduced into the modified polyurethane is a commonly used halogen-free flame retardant among nitrogen-based flame retardants, the melamine and polyphosphoric acid work together to form melamine phosphate, where melamine and phosphoric acid produce a synergistic effect. Additionally, during the experiment, the cable... Carbon detection showed that the carbonization rate of melamine phosphate reached 45% at 700℃, which also affected its melting behavior. This is mainly because melamine phosphate can decompose to produce a network polymer, thereby greatly increasing the carbonization rate of the polymer and further improving the flame retardant rating of the cable. In the modified polyurethane, the grafted intermediate I contains a large number of Si-O bonds, and the silicon-oxygen chain has a helical configuration. The flexibility of the molecular chain is greater than that of C-C bonds or Si-C bonds, exhibiting excellent physical and mechanical properties. Furthermore, the bond energy of the silicon-oxygen bond is greater than that of C-C bonds or Si-C bonds, thus improving the cable's flexibility. The amino groups on intermediates I and II react with the isocyanate groups on toluene-2,4-diisocyanate, through… After the raw materials of the cable are mixed evenly and then extruded through a screw extruder, the components of the cable are fused together. The modified polyurethane is evenly distributed on the outer lining of the cable to form a mesh support with silicon elements as nodes, thereby improving the wear resistance of the cable.

[0078] In Comparative Example 2, the absence of intermediate I prevented the formation of a silicon-based mesh support structure on the cable liner, resulting in reduced abrasion resistance and flexural properties. Furthermore, the long straight-chain structure of intermediate I allows it to cross-link with adjacent molecules, further enhancing the cable's tensile strength.

[0079] Comparative Example 3, due to the absence of intermediate II, lacked melamine phosphate on the outer side of the cable, resulting in a poorer flame retardant rating.

[0080] The above description is merely an example and illustration of the structure of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

[0081] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0082] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A flexible, wear-resistant, reel-type power cable for military use in the field, characterized in that, include: The conductive component (1) is composed of several tin-plated conductors (101), all of which are spiral structures, and each of the tin-plated conductors (101) is covered with an insulating sleeve (102). Reinforcing ribs (2), the number of reinforcing ribs (2) is several, and several reinforcing ribs (2) are alternately distributed between multiple tin-plated conductors (101); A flame-retardant layer (3) is wrapped around the outside of the conductive component (1) and the reinforcing rib (2); The outer liner (4) is wrapped around the outside of the flame-retardant layer (3) and is made of polyurethane composite material; The polyurethane composite material is composed of modified polyurethane, viscose fiber, polyvinyl chloride and additives in a weight ratio of 20-30:4-6:20-30:1-2. The synthesis of the modified polyurethane includes the following steps: S1. Weigh 100-200 parts by weight of octamethylcyclotetrasiloxane and 100-200 parts by weight of 1,3-bis(aminopropyl)tetramethyldisiloxane, add them to a three-necked flask and stir. Under nitrogen protection, raise the temperature of the three-necked flask to 100-110℃, add 0.2-0.4 parts by weight of catalyst to the three-necked flask, react for 10-14 hours, and then obtain intermediate I after post-treatment. S2. Weigh 10-20 parts of melamine, 30-60 parts of deionized water, 8-16 parts of polyphosphoric acid and 15-30 parts of zinc phosphate solution by weight, add them to a three-necked flask and stir. Raise the temperature of the three-necked flask to 95-105℃ and react for 2-3 hours. After post-processing, intermediate II is obtained. S3. Weigh out 30-60 parts by weight of intermediate I, 30-60 parts by weight of intermediate II, 20-40 parts by weight of toluene-2,4-diisocyanate, 90-180 parts by weight of tetrahydrofuran, and 3-5 parts by weight of acetic acid. Add them to a three-necked flask and stir. React for 4-6 hours. After post-treatment, the modified polyurethane is obtained.

2. The field-use military flexible abrasion-resistant reel power cable according to claim 1, characterized in that, The additive is prepared by uniformly mixing a crosslinking agent and a lubricant at a weight ratio of 1:1-1.

5. The crosslinking agent is composed of one or more of trimethylolpropane, polyethylene glycol, and p-toluenesulfonic acid, and the lubricant is composed of one or more of zinc stearate and calcium stearate.

3. The field-use military flexible abrasion-resistant reel power cable according to claim 1, characterized in that, The catalyst in step S1 is one of tetramethylammonium hydroxide silanolate or tetraethylammonium hydroxide silanolate.

4. The field-use military flexible abrasion-resistant reel power cable according to claim 1, characterized in that, The post-processing operation of step S1 is as follows: after the reaction is completed, the temperature of the three-necked flask is raised to 138-142°C, and the mixture is distilled under reduced pressure until no liquid flows out. The distillate is discarded, and the temperature of the three-necked flask is raised to 150-155°C and the mixture is distilled under reduced pressure to obtain intermediate I.

5. The field-use military flexible abrasion-resistant reel power cable according to claim 1, characterized in that, In step S2, the zinc phosphate solution is a phosphoric acid solution with a zinc content of 13 wt%, prepared by completely dissolving 2-4 parts by weight of zinc oxide in 13-26 parts by weight of phosphoric acid.

6. The field-use military flexible abrasion-resistant reel power cable according to claim 1, characterized in that, The post-processing operation of step S2 is as follows: After the reaction is completed, the system is cooled to room temperature, ammonia water is slowly added to the three-necked flask to adjust the pH of the reaction system in the three-necked flask to 6-7, the mixture is filtered, the filter cake is washed with an ammonia solution of pH 6-7 and then dried, the filter cake is placed in a drying oven at 90-110℃ and dried for 8-10 hours, then pulverized to obtain intermediate II.

7. The field-use military flexible abrasion-resistant reel power cable according to claim 1, characterized in that, The post-processing operation of step S3 is as follows: After the reaction is completed, add 90-180 parts by weight of drinking water to a three-necked flask, stir for 10-20 minutes, raise the temperature of the three-necked flask to 40-50°C, distill under reduced pressure until no liquid flows out, filter, rinse the filter cake with drinking water and dry it, place the filter cake in a drying oven at 100-120°C and dry it for 10-12 hours to obtain modified polyurethane.

Citation Information

Patent Citations

  • Electric wire material and preparation method thereof

    CN112920592A

  • High-tensile, bending-resistant, signal-interference-resistant and ultraviolet-resistant reel cable

    CN209822317U